PUBLIC PARTICIPATION MANAGEMENT IN DEVELOPMENT PLANNING AT BAPPEDA GORONTALO CITY - Ikram Muhammad; Falha Mustapa; Karlina Napu (LP2M Universitas Bina Mandiri Gorontalo, 2024)
This study aims to analyze the management of public participation in the formulation of development planning at the Regional Development Planning Agency (Bappeda) of Gorontalo City. The study employs a qualitative approach with a case study design, enabling an in-depth exploration of processes, actor dynamics, and institutional contexts in the implementation of public participation. Data were collected through in-depth interviews, observation, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the management of public participation is carried out through three main stages: planning, implementation, and evaluation with follow-up actions. At the planning stage, Bappeda conducts stakeholder mapping and develops participation mechanisms based on regulatory frameworks. During the implementation stage, participation is facilitated through Musrenbang (Development Planning Deliberation) and public consultation forums, although challenges remain in terms of representation and the quality of participation. At the evaluation stage, some community proposals are accommodated in planning documents; however, feedback mechanisms remain suboptimal. This study concludes that public participation is still at a consultative level and has not yet fully achieved substantive participation. Therefore, strengthening institutional capacity, improving the quality of facilitation, and developing more inclusive and transparent participation mechanisms are necessary to enhance the effectiveness of regional development planning.